2005
DOI: 10.1095/biolreprod.105.042747
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Rhox5 Homeobox Gene in Primary Granulosa Cells: Preovulatory Expression and Dependence on SP1/SP3 and GABP1

Abstract: Homeobox genes encode transcription factors that regulate embryonic development and postnatal events. Rhox5 (previously called Pem), the founding member of a homeobox gene cluster that we recently identified on the X chromosome, is selectively expressed in granulosa cells in the ovary and other somatic-cell types in other reproductive organs. In this report, we investigate its regulation in granulosa cells in the rat ovary. We found that Rhox5 expression in the ovary is governed by the Rhox5 distal promoter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 67 publications
4
49
0
Order By: Relevance
“…K-RAS signaling is also required for the phosphorylation and activation of MAPK3/1 (ERK1/2), which, in turn, is required for granulosa cells to promote LH-induced resumption of germ cell meiosis, ovulation, and luteinization (Fan et al 2009). Gonadotropin treatment induces peak MAPK3/1 activity in rodent granulosa cells at a similar time point as that for maximal Pd mRNA levels (MacLean et al 2005b, Fan et al 2009), suggesting the possibility that Pd transcription also requires MAPK3/1. While this has not been tested, it is known that other components of the MAP kinase pathway -namely the stress-activated protein kinase/c-Jun amino-terminal kinases -are required for Pd transcription (Rao et al 2002a, MacLean et al 2005b).…”
Section: The Pdmentioning
confidence: 90%
See 4 more Smart Citations
“…K-RAS signaling is also required for the phosphorylation and activation of MAPK3/1 (ERK1/2), which, in turn, is required for granulosa cells to promote LH-induced resumption of germ cell meiosis, ovulation, and luteinization (Fan et al 2009). Gonadotropin treatment induces peak MAPK3/1 activity in rodent granulosa cells at a similar time point as that for maximal Pd mRNA levels (MacLean et al 2005b, Fan et al 2009), suggesting the possibility that Pd transcription also requires MAPK3/1. While this has not been tested, it is known that other components of the MAP kinase pathway -namely the stress-activated protein kinase/c-Jun amino-terminal kinases -are required for Pd transcription (Rao et al 2002a, MacLean et al 2005b).…”
Section: The Pdmentioning
confidence: 90%
“…Subsequent work demonstrated that Rhox5 is not only expressed in a subset of T-cell lymphomas, but it is widely expressed in tumors derived from many different cell types and tissue origins (Wilkinson et al 1990, Maiti et al 1996b, Wayne et al 2002a. Its ubiquitous expression in tumors may derive, in part, from its ability to be induced by the Ras proto-oncogene (Rao et al 2002a, MacLean et al 2005b. RHOX5 may also have a causal role in tumor formation, as it induces an immune response in mouse tumors (Ono et al 2000), and it physically interacts with proteins involved in malignancy (Lemmens et al 2001, Guo et al 2005).…”
Section: Rhox5mentioning
confidence: 99%
See 3 more Smart Citations